Development of Observation-Based Hybrid Learning Modules as Learning Media for Biodiversity Materials - Nafi'ah, Miftahun; Ngabekti, Sri; Widiatningrum, Talitha (Universitas Negeri Semarang, 2022)
This study aims to develop an observation-based hybrid learning module as a learning media for biodiversity material. This study uses research and development methods. This research was conducted at MA Darul Ulum Purwogondo Jepara. The subjects of this study consisted of a small-scale trial subject with 20 students and a large-scale trial subject with 68 students. Instruments and data collection techniques in the form of questionnaires and tests of students' cognitive learning outcomes obtained from the pretest and posttest scores. The results showed that (1) the observation-based hybrid learning module was declared valid by validators of media experts and material experts with an average score of 94.4%. (2) The results of the readability analysis of the module meet the very good criteria based on the teacher's response of 97.5% and the student's response of 83.6%. (3) The results of the feasibility analysis of the module based on the teacher's response of 95% and the student's response of 82.1% indicate the module is very feasible. (4) The results of the analysis of the effectiveness of the module to improve students' cognitive learning outcomes are the N-gain value of 0.70 with high criteria. The results of this study indicate that the observation-based hybrid learning module is feasible and effective to be used as a learning media for biodiversity material to improve students' cognitive learning outcomes.